Simultaneous exposure to chronic irradiation and simulated microgravity differentially alters immune cell phenotype in mouse thymus and spleen. (February 2021) - Sadhukhan, Ratan; Majumdar, Debajyoti; Garg, Sarita; Landes, Reid D.; McHargue, Victoria; Pawar, Snehalata A.; Chowdhury, Parimal; Griffin, Robert J.; Narayanasamy, Ganesh; Boerma, Marjan; Dobretsov, Maxim; Hauer-Jensen, Martin; et al.
Abstract: Deep–space missions may alter immune cell phenotype in the primary (e.g., thymus) and secondary (e.g., spleen) lymphoid organs contributing to the progression of a variety of diseases. In deep space missions, astronauts will be exposed to chronic low doses of HZE radiation while being in microgravity. Ground-based models of long-term uninterrupted exposures to HZE radiation are not yet available. To obtain insight in the effects of concurrent exposure to microgravity and chronic irradiation (CIR), mice received a cumulative dose of chronic 0.5 Gy gamma rays over one month ± simulated microgravity (SMG). To obtain insight in a dose rate effect, additional mice were exposed to single acute irradiation (AIR) at 0.5 Gy gamma rays. We measured proportions of immune cells relative to total number of live cells in the thymus and spleen, stress level markers in plasma, and change in body weight, food consumption, and water intake. CIR affected thymic CD3+/CD335+ natural killer T (NK-T) cells, CD25+ regulatory T (Treg) cells, CD27+/CD335- natural killer (NK1) cells and CD11c+/CD11b- dendritic cells (DCs) differently in mice subjected to SMG than in mice with normal loading. No such effects of CIR on SMG as compared to normal loading were observed in cell types from the spleen. Differences between CIR and AIR groups (both under normal loading) were found in thymic Treg and DCs. Food consumption, water intake, and body weight were less after coexposure than singular or no exposure. Compared to sham, all treatment groups exhibited elevated plasma levels of the stress marker catecholamines. These data suggest that microgravity and chronic irradiation may interact with each other to alter immune cell phenotypes in an organ–specific manner and appropriate strategies are required to reduce the health risk of crewmembers.